Implementation of Qur’anic Principles in Modern Government Systems: A Case Study of Muslim Countries - Ahmad Zuhdi; Helmina Helmin; Hakki Akmal Labib; Jasafat Jasafat (Journal of Noesantara Islamic Studies, 2025)
The integration of Qur’anic principles into modern government systems represents a critical area of inquiry in contemporary Islamic governance studies. Muslim-majority countries have sought to align governance practices with Islamic values while addressing the challenges of modern state systems. This research examines the implementation of Qur’anic principles, such as justice (adl), consultation (shura), and accountability (muhasabah), in the governance frameworks of selected Muslim countries. The study explores how these principles are operationalized within modern political and legal systems to balance Islamic ideals with global governance standards. The research aims to assess the extent to which Qur’anic principles influence contemporary governance structures and identify best practices and challenges in their application. Employing a qualitative case study methodology, the study analyzes governance models in Malaysia, Turkey, and Saudi Arabia through primary legal documents, government policies, and interviews with policymakers and scholars. The findings reveal significant variations in the operationalization of Qur’anic principles across the selected countries, reflecting differences in political systems, historical contexts, and interpretations of Islamic law. The study concludes that effectively integrating Qur’anic principles into modern governance requires context-specific approaches that align with both Islamic teachings and contemporary governance standards.